Analysis of the digital scientific journals of the Index of Mexican Journals of Scientific and Technological Research: Compliance with institutional criteria and adoption of digital publishing parameters - Guerra González, Jenny Teresita (Revista General de Información y Documentación, 2016)
Is analyzes the fulfillment of general and specific criteria from the digital scientific journals indexed in the Index of Mexican Journals of Scientific and Technological Research managed by the Council National of Science and Technology. The paper describes a first moment -in particular criteria with which the CONACYT evaluates the journals published online to integrate them in the Index. Later confronts issues that meet the existing four digital magazines in it with electronic versions of magazines areas belonging to these publications. Which today employ digital magazines worldwide to distinguish themselves visible and the addition of four parameters (mobile versión;HTML desktop versión; availability of items in XML and inclusion of buttons sharing in social networks) is also studied. Some of the results obtained are: none of the four magazines studied meets all the parameters necessary to join eleven publishers or stay in the IRMICT. Only one of the magazines studio features mobile version, three of them incorporate buttons sharing of content on social networks, it has the same number and no HTML version allows downloading in XML format.
Keywords: Scientific journal; Digital journals; Digital parameters; CONACYT; Mexico